GRAIN-SIZE STATISTICAL PARAMETERS OF SANDY SEDIMENT IN KUALA GIGIENG, ACEH BESAR DISTRICT - Syahrul Purnawan; Haekal A. Haridhi; Ichsan Setiawan; . Marwantim (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2015)
Study of sediment distribution at Kuala Gigieng was to assess the information of sediment related to the occurrence of hydro-oceanographic processes. The sediment samples were collected from nine stations using coring method. Granulometric method was used to analyze the grain size distributions. The results showed different sediment distribution patterns in each area at estuary Kuala Gigieng. The outer area of estuary indicated skewed to coarse grains, while at the inner area of estuary indicated skewed to fine grains. Different sediment load transport process was suggested as the cause of differentiated sediment characters. Keywords: granulometry, grain size, sediment statistic, Kuala Gigieng